Peningkatan Hasil Belajar Mata Pelajaran Matematika melalui Pendekatan SAVI (Somatis, Auditori, Visual, Intelektual) pada Siswa Kelas V-A MIN I Yogyakarta - Tri Suhartiningsih (Jurnal Pendidikan Madrasah, 2019)
The purpose of this study was to determine the learning outcomes of VA MIN I Yogyakarta class students with the Somatic Visual Intellectual Education (SAVI) approach with the Class Action Research method (classroom Action Research). It can be seen from the pre-action class score of 72.14 with the completeness percentage of 62.96%. With the increase in mathematics learning outcomes in the learning cycle 2 times. Somatic learning students want to move, want to understand the characteristics of building space with a visual model capable of attracting students to the subject matter, the auditory model helps students capture material and trains students to evoke imagination in determining the properties of building space, while the intellectual model helps students learn by understanding and mastering the material. I obtained the mean value of the class s 84.81 with a percentage of 81.49%. Cycle II obtained a class average value of 91.85 with a completeness percentage of 96.29%. The limitation in this study is only using the SAVI approach in Yogyakarta MIN I VA class 2018/2019 class students and not yet comprehensive.